Aglaonema costatum f. concolor Nicolson (Araceae): a new record for the flora of Vietnam - Truong, Luu Hong; Thien, Van Hong; Thanh, Bui Ngoc; Kien, Le Thuan; Cuong, Truong Quang; Nam, Le Canh (Academia Journal of Biology, 2019)
Aglaonema costatum f. concolor is reported as a new record for the flora of Vietnam. The taxon was recently found in Phong Nha - Ke Bang National Park, Quang Binh Province. It is illustrated with detailed photographs of key morphological characters taken from the field. A key to all known taxa of Aglaonema in Vietnam is given.